Remediation of the areas contaminated by depleted uranium ammunition - Inđić, Dejan R. (Vojnotehnički glasnik / Military Technical Courier, 2021)
Introduction/goal: The consequences of the NATO aggression on the Republic of Serbia (then part of FR Yugoslavia) in 1999 are still being considered, especially from the aspect of the use of illicit means such as cluster and graphite bombs, depleted uranium ammunition (DUA), etc. There is no doubt that the use of depleted uranium, as a type of weapon of mass destruction (radiological weapon) is mostly in the focus of public interest. The amount of DUA used and the consequences of its use have not yet been fully proven (even after 20 years), but it can be said with certainty that it has caused certain side effects. The units of the Yugoslav Army at that time were mostly the target of this type of ammunition and certainly suffered the greatest consequences. However, DUA also targeted infrastructure facilities, base stations, television transmitters, and agricultural land. Methods: Special scientific methods (mainly analysis and synthesis methods) and empirical methods (content analysis method and observation method) were used in the paper. Results: The consequences of the effect of DUA on people, material goods, and environmental degradation are considered as well as the directions of further work in this area. Conclusion: The paper presents the results of the radiological reconnaissance and radiological decontamination of the contaminated DUA areas, which were carried out by ABH service units (then ABHO) with the help of other branches and services of the Serbian Army, as well as the institutions of the Republic of Serbia (INS „Vinča“, MMA, etc.).